2018
DOI: 10.1194/jlr.r082735
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteryl ester transfer protein and its inhibitors

Abstract: Most of the cholesterol in plasma is in an esterified form that is generated in potentially

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 119 publications
1
49
0
Order By: Relevance
“…Overall, CETP inhibitors that have reached late stage clinical development are categorized into CETP inhibitors (torcetrapib, evacetrapib and anacetrapib) and modulators (dalcetrapib) (14). Despite the beneficial influence on cholesterol metabolism, off-target effects and lack of reduction in CV events and mortality (with torcetrapib, dalcetrapib and evacetrapib) have highlighted the complex, unclear beneficial mechanism of CETP inhibition (186 Through Lipid-modification) study, demonstrating a significant 9% proportional reduction of major coronary events upon anacetrapib administration (100 mg), reported no data on hsCRP.…”
Section: Cholesteryl Ester Transfer Protein Inhibitorsmentioning
confidence: 99%
“…Overall, CETP inhibitors that have reached late stage clinical development are categorized into CETP inhibitors (torcetrapib, evacetrapib and anacetrapib) and modulators (dalcetrapib) (14). Despite the beneficial influence on cholesterol metabolism, off-target effects and lack of reduction in CV events and mortality (with torcetrapib, dalcetrapib and evacetrapib) have highlighted the complex, unclear beneficial mechanism of CETP inhibition (186 Through Lipid-modification) study, demonstrating a significant 9% proportional reduction of major coronary events upon anacetrapib administration (100 mg), reported no data on hsCRP.…”
Section: Cholesteryl Ester Transfer Protein Inhibitorsmentioning
confidence: 99%
“…Circulating plasma lipoproteins are remodeled not only by the exchange of their surface components, but also by their core components, mediated by the cholesteryl ester transfer protein (CETP), whose properties are summarized by Rye and her colleagues (7). Thus the triglycerides of the triglyceride rich lipoproteins are exchanged for cholesteryl esters of the smaller lipoproteins, notably HDL.…”
Section: Transfer Of Lipid From Diet To Tissuementioning
confidence: 99%
“…Further supporting the hypothesis that CETP inhibition is antiatherogenic came from multiple genetic studies in humans. Large genetic studies consistently showed favorable lipoprotein profiles and lowered ASVD risk in individuals with CETP polymorphisms that reduced CETP activity [6]. Particularly strong evidence was provided in the Copenhagen City Heart Study, in which 10,261 people were followed for up to 34 years [7].…”
mentioning
confidence: 99%
“…With this strong body of evidence for CETP inhibition being athero-protective, what then is the mode of action of CETP such that CETP inhibition should be beneficial? CETP promotes the exchange of neutral lipids between HDL and non-HDL lipoproteins, consisting of lipoprotein particles containing apolipoprotein B100 (apoB100) [6,8]. The non-HDL lipoproteins include VLDL, their remnants, and LDL particles, all of which are pro-atherogenic.…”
mentioning
confidence: 99%
See 1 more Smart Citation